Detecting Fraudulent Financial Reporting The Construction Sector In Indonesia: Fraud Triangle - Eko Pujiyono Yono; Indira Januarti Indira (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2024)
The category of fraud that has the largest number of losses is financial statement fraud. Apart from being financially detrimental to a company, fraudulent financial reports can also threaten the company's sustainability. Examining the influence of financial targets, financial stability, external pressure, industry nature and rationalization on financial report fraud (F-Score) in construction sector companies in Indonesia is the aim of this research. This research is quantitative, with secondary data types. The number of samples used was 83 from the total construction sector companies. The research results show that financial stability has a positive effect, while financial targets, external pressure, nature of industry and rationalization have a negative and insignificant effect on fraudulent financial reporting.